Pelaksanaan lelongan awam daripada perspektif pentadbir tanah – kajian kes di Pejabat Daerah dan Tanah Kuantan - Aris, Khairun Nissa (2009)
Land is everything. Land is a scarce commodity more valuable than money due to its nature of being durable and do not depreciate in value. Land is often regarded as good collateral for loans through legal process called charge. Government guarantee chargee’s right in the event of default by chargor by way of enacting the National Land Code 1965. Chargee may apply to the Land Office for the land to be sold by way of public auction for Land Office title, likewise to the High Court for Registrar Title. Land and Mines Director General also issue circulars to further guide Land Administrators in the due processes of public auction. The study involves a period of five years from 2004 to 2008 to dig issues and problems and formulate recommendations.